How important are consumer confidence shocks for the propagation of business cycles in Bulgaria? - Aleksandar Vasilev (University of Lincoln, Lincoln International Business School, Lincoln Economics and Finance Research Group (LEAF), 2019)
This paper takes an otherwise standard real-business-cycle setup with government sector, and augments it with shocks to consumer confidence to study business cycle fluctuations. A surprise increase in consumer confidence generates higher utility, as the household values consumption more in that scenario. As a test case, the model is calibrated to Bulgaria after the introduction of the currency board (1999-2018). We find that shocks to consumer confidence by themselves cannot be the main driving force behind business cycle fluctuations, but when combined with technology shocks, model performance improves substantially. Therefore, allowing for additional factors, such as consumer confidence, to interact with technology shocks can be useful in explaining business cycle movements.
Keywords: E32; E62; E21; 330; consumer confidence shocks; business cycles; Bulgaria